A new labdane-type diterpenoid from the leaves of Vitex negundo L. Issue 14 (18th July 2021) - Sichaem, Jirapast; Nguyen, Hung-Huy; Nguyen, Van-Huong; Mac, Dinh-Hung; Mai, Dinh-Tri; Nguyen, Hoang-Chuong; Tran, Thi-Ngoc-Mai; Pham, Nguyen-Kim-Tuyen; Nguyen, Huu-Hung; Niamnont, Nakorn; Duong, Thuc-Huy
Abstract: A new labdane-type diterpenoid, named vitexnegundin (1 ), along with seven known compounds, including vitexilactone (2 ), vitetrifolin D (3 ), 13-hydroxy-5(10), 14-halimadien-6-one (4 ), (rel 3 S, 5 S, 8 R, 9 R, 10 S )-3, 9-dihydroxy-13(14)-labden-16, 15-olide (5 ), artemetin (6 ), vitexcarpin (7 ) and penduletin (8 ), were isolated from the leaves of Vitex negundo L. Their structures were elucidated by using spectroscopic methods, X-ray crystallographic analysis and comparison with those reported in the literature. Moreover, all isolated compounds 1–8 were evaluated for their antimicrobial activity against ESBL-producing Escherichia coli strain and methicillin-resistant Staphylococcus aureus . Graphical Abstract: